The Spatial and temporal distribution of purse-seine yellowfin tuna (Thunnus albacares) catches in relation to AVHRRderived SST in the eastern tropical Pacific Ocean (Revista Científica Ciencias Naturales y Ambientales, 2017)
Purse-seine yellowfin tuna (Thunnus albacares) catch and effort data and satellite monthly composite images of the Advanced Very High Resolution Radiometer (AVHRR) derived sea surface temperature (SST) were used to examine the relationship between the aggregation of yellowfin and the distribution of SST in the eastern tropical Pacific during the period 1995-2003. Monthly catch per unit effort (CPUE) values were calculated as the catch in metric tonnes/number of fishing days in a 1º latitude x 1º longitude grid and used as the relative abundance index. In total, 33,542 purseseine yellowfin CPUE data were used. Results obtained allow establishing the SST range between 26ºC and 30ºC as the “preferred” thermal range for yellowfin tuna in the eastern tropical Pacific, and the SST range between 28ºC and 30ºC as the most favorable SST range of yellowfin fishing success. The consistent occurrence of yellowfin tuna in the relatively shallow mixed surface layer (≈40-50 m) of homogeneous temperature predominant in the eastern tropical Pacific suggests that the “preferred” SST range for yellowfin found in this study may be representative of the optimal thermal habitat of this species.
Keywords: ETP; Purse-seine fishery; Satellite oceanography; SST; Yellowfin tuna